Anomalous Origin of Left Coronary Artery from the Pulmonary Artery (ALCAPA) in an Infant - A Case Report (Bangladesh Journal of Child Health, 2017)
Abstract not availableBangladesh J Child Health 2016; VOL 40 (1) :39-43